Effect of pulsation on flow and thermal characteristics of a wall jet. (November 2022) - Marzouk, Saloua; Hnaien, Nidhal; Aich, Walid; Alshammri, Naif; Kolsi, Lioua
Abstract: In the current investigation, a computational analysis of the thermal and dynamic characteristics of a pulsed incompressible laminar wall jet is performed under a forced convection regime. The considered wall is isothermal with a temperature dissimilar from that of the surrounding fluid. The nozzle outlet is marked by a periodic and parabolic profile of the longitudinal velocity as well as a uniform temperature. The dimensionless transport equations governing the heat and momentum transfer phenomenon are solved using the finite difference method with irregular mesh. Our results are validated against those which emanate from the non-pulsed jet in its different regions. The spatial and temporal evolution of the wall jet characteristics such as the velocities, the friction coefficient, the jet spreading, and the Nusselt number are presented and analyzed. It was revealed that the inclusion of pulsation leads to the spreading of the jet and the curtailment of the potential core length relative to a steady jet. Moreover, the pulsation strengthens the entrainment and mixing of the ambient fluid and therefore improves the heat transfer in the potential cone area.